2017
DOI: 10.1103/physreve.95.042106
|View full text |Cite
|
Sign up to set email alerts
|

Tricritical behavior of nonequilibrium Ising spins in fluctuating environments

Abstract: We investigate the phase transitions in a coupled system of Ising spins and a fluctuating network. Each spin interacts with q neighbors through links of the rewiring network. The Ising spins and the network are in thermal contact with the heat baths at temperatures T_{S} and T_{L}, respectively, so the whole system is driven out of equilibrium for T_{S}≠T_{L}. The model is a generalization of the q-neighbor Ising model [A. Jędrzejewski et al., Phys. Rev. E 92, 052105 (2015)PLEEE81539-375510.1103/PhysRevE.92.05… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…It has been shown that on contrary to the models investigated previously by Lee et al [1], the kinetic model studied in Jȩdrzejewski et al [3] is an non-equilibrium one and corresponds to the infinite temperature T L of links. Furthermore, it has occurred that there is a critical temperature T * L at which switch from discontinuous to continuous phase transition is observed (so called tricritical point) [4]. However, the question arose if such a tricriticality could be exclusively explained on the basis of non-equilibrium driving.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that on contrary to the models investigated previously by Lee et al [1], the kinetic model studied in Jȩdrzejewski et al [3] is an non-equilibrium one and corresponds to the infinite temperature T L of links. Furthermore, it has occurred that there is a critical temperature T * L at which switch from discontinuous to continuous phase transition is observed (so called tricritical point) [4]. However, the question arose if such a tricriticality could be exclusively explained on the basis of non-equilibrium driving.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore results obtained in Jȩdrzejewski et al [3], showing that kinetic Ising model with Metropolis dynamics can also display discontinuous phase transitions, were puzzling and confusing. To solve this puzzle a new generalized model with two heat baths-one for the Ising spins at temperature T s and second for links of the graph at temperature T L , has been recently proposed [4]. It has been shown that on contrary to the models investigated previously by Lee et al [1], the kinetic model studied in Jȩdrzejewski et al [3] is an non-equilibrium one and corresponds to the infinite temperature T L of links.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations